EVALUATION OF NATURAL RADIOACTIVITY LEVELS AND CORRESPONDING DOSE RATES IN SOIL SAMPLES COLLECTED FROM DUHOK PROVINCE, KURDISTAN REGION-IRAQ - Hasan Jarjes, Azhen; Ahmed, SHAYMA; A. H. Alhamd, Walat (Science Journal of University of Zakho, 2025)
ABSTRACT: One of the significant concerns in daily human life is exposure to elevated levels of natural background radiation, both outdoors and indoors. This radiation primarily originates from primordial radioisotopes such as Uranium, Thorium, and Potassium, which emit harmful gamma rays. This study examines the activity concentrations of natural radioisotopes Ra-226, Th-232, and K-40 in soil samples collected from various locations in the Duhok Governorate, northern Iraq. To the best of our knowledge, comprehensive studies on these three radioisotopes in this region are limited, highlighting the novelty of this work. Gamma-ray spectrometry using a high-purity NaI(Tl) detector was employed to measure activity concentrations. Several radiological parameters were assessed, including the radium equivalent activity (Raeq), indoor and outdoor absorbed dose rates (Din, Dout), internal and external hazard indices (Hin, Hex), and annual effective dose rates (AEin, AEout). Results showed average concentrations of 30 Bq/kg for Ra-226, 56 Bq/kg for Th-232, and 145 Bq/kg for K-40. While Ra-226 and K-40 levels were within global safety limits, Th-232 exceeded recommended values, raising potential health concerns